The Influence of Financial Literacy and Educational Background on the Financial Governance of Nagari Owned Enterprises - Wiwik Andriani; Rangga Putra Ananto; Zahara Zahara; Dandi Aprila (Yayasan Ilomata, 2023)
Initial observations carried out at Nagari-Owned Enterprises (BUMNag) in Nagari Z found that BUMNag managers' understanding of good financial governance still needed to be improved, causing the financial governance of BUMNag in Nagari Z not to be improved. This is due to a need for more training regarding financial literacy and a mismatch in the educational background of the BUMNag managers. This research aims to determine and analyze the influence of financial literacy and educational background on financial governance in Nagari-owned enterprises (BUMNag) in Nagari Z. The approach used in this research is quantitative with a survey method. The data used in this research is primary data obtained from distributing questionnaires to managers of Nagari-owned enterprises in Nagari Z with 83 respondents. The sampling method used in this research is the stratified random sampling method. The research results show that financial literacy and educational background partially influence the financial governance of BUMNag in Nagari Z. In line with these results, financial literacy and educational background simultaneously influence the financial governance of BUMNag in Nagari Z.